Investigation of intermolecular proton exchange 3,6-di-tert-butyl-2-hydroxyphenoxyl with phenol by ESR spectroscopy method - Nikolskiy, S.N.; Tur, A.A.; Yelchibekova, A.A.; Kutzhanova, K.Zh.; Masalimov, A.S. (KSU Publ., 2015)
The intermolecular proton exchange reactions was study between radical 3,6-di-tert-butyl-2-hydroxyphenoxyl and melt of phenol by ESR spectroscopy method. Kinetic parameters of the intermolecular proton exchange reactions was presented. Phenol has been weaker protolytic reactivity than of carboxylic acids and phenol as a medium slows intermolecular proton exchange were shown.
3,6-Ди-үш.бутил-2-гидроксифеноксилдің фенолмен молекулааралық протон алмасуын ЭПР-спектроскопия əдісімен зерттеу
Исследование межмолекулярного протонного обмена 3,6-ди-трет.бутил- 2-гидроксифеноксила с фенолом методом ЭПР-спектроскопии
Keywords: ESR-spectroscopy; spin probe; semiquinone radical; phenol; 3,6-di-tert-butyl-2-hydroxyphenoxyl; OH-acids; proton exchange reactions; Bloch equation